A novel circadian daylight metric for building design and evaluation. (15th February 2017) - Konis, Kyle
Abstract: This paper extends the applicability of emerging frameworks for evaluating the non-visual effects of light through the development of a novel area-based daylighting metric addressing goals of human circadian stimulus and entrainment in buildings. Procedures using annual, climate-based daylight modeling of eye-level light exposures are developed to analyze and map indoor environments in regard to spatial and seasonal changes in the availability of a circadian-effective daylight stimulus. Because the biological effects of light exposure are not instantaneous, a novel approach is developed to assess the duration of an effective stimulus on a daily basis, as well as the frequency an effective stimulus is present over the course of a year. Results can be used to identify and visually examine building zones where long-term occupancy may lead to disruption of the circadian system in the absence of supplemental electrical lighting capable of effective circadian stimulus. The metric and visualization techniques are implemented in a parametric, simulation-based workflow utilizing publicly available software tools. The workflow can be used to assess and differentiate the performance of various daylighting strategies during the design phases of a project, or to examine existing spaces. The applicability of the workflow is demonstrated using two example models: a portable school classroom, and a generic open-plan commercial office floor plate. Highlights: A novel circadian daylight metric is presented. A spatial classification system and visualization techniques are developed. A simulation approach is demonstrated for informing design using circadian metrics. The metric enables area-based summary of circadian effectiveness.